2012
DOI: 10.1007/s00253-012-4438-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of 3-O-xylosyl quercetin in Escherichia coli

Abstract: Quercetin, a flavonol aglycone, is one of the most abundant flavonoids with high medicinal value. The bioavailability and pharmacokinetic properties of quercetin are influenced by the type of sugars attached to the molecule. To efficiently diversify the therapeutic uses of quercetin, Escherichia coli was harnessed as a production factory by the installation of various plant and bacterial UDP-xylose sugar biosynthetic genes. The genes encoding for the UDP-xylose pathway enzymes phosphoglucomutase (nfa44530), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 40 publications
0
59
0
1
Order By: Relevance
“…We found that the quantities of UDP-glucuronic acid synthesized increased following overexpression of ugd and deletion of arnA, which, in turn, led to increased quercetin 3-O-xyloside production. Pandey et al (19) increased the pool of UDP-glucose instead of UDP-glucuronic acid by mutating several genes and overexpressing galU (encoding glucose 1-phosphate uridyltransferase). Although the pool of UDP-glucose increased, there was likely limited conversion of UDP-glucose into UDP-glucuronic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the quantities of UDP-glucuronic acid synthesized increased following overexpression of ugd and deletion of arnA, which, in turn, led to increased quercetin 3-O-xyloside production. Pandey et al (19) increased the pool of UDP-glucose instead of UDP-glucuronic acid by mutating several genes and overexpressing galU (encoding glucose 1-phosphate uridyltransferase). Although the pool of UDP-glucose increased, there was likely limited conversion of UDP-glucose into UDP-glucuronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…However, other flavonoid O-glycosides, such as flavonoid O-rhamnoside and flavonoid O-xyloside, have been synthesized using E. coli by expressing plant UGTs along with the corresponding nucleotide biosynthesis genes (5,(17)(18)(19). The biological activities of a variety of flavonoid O-glycosides have been elucidated (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Therefore, chemical synthesis is not suitable for the production of flavonoids to be incorporated into food ingredients or cosmetics. Among the microorganisms used for the biosynthesis of natural products, Escherichia coli has been the most intensively investigated host because of its genetic tractability and favorable fermentation properties (12).…”
mentioning
confidence: 99%
“…4A), as described in materials and methods in the supplemental material. The optimal growth conditions described in our previous report (21) were used for the bioconversion. The HPLC-PDA analysis of in vivo reactions showed the production of four phloretin glucosides with the same retention time as in in vitro reactions ( Fig.…”
mentioning
confidence: 99%